2015
DOI: 10.1007/s00198-015-3029-x
|View full text |Cite
|
Sign up to set email alerts
|

RANKL and OPG gene polymorphisms: associations with vertebral fractures and bone mineral density in premenopausal systemic lupus erythematosus

Abstract: Our study provides novel data demonstrating that RANKL/OPG genetic variations appear to play a role in bone remodeling, particularly in its major complication, fracture, in premenopausal patients with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 36 publications
2
24
2
1
Order By: Relevance
“…1). Finally, a total of 10 studies were enrolled in this meta-analysis 8, 10–15, 2325 , and a total of 12 SNPs with genotyping data in at least one study were meta-analyzed. Supplementary Table 2 listed the detailed information of recruited studies for this meta-analysis, i .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). Finally, a total of 10 studies were enrolled in this meta-analysis 8, 10–15, 2325 , and a total of 12 SNPs with genotyping data in at least one study were meta-analyzed. Supplementary Table 2 listed the detailed information of recruited studies for this meta-analysis, i .…”
Section: Resultsmentioning
confidence: 99%
“…For example, one recent published GWAS using European and east Asian cohorts identified 56 loci associated with BMD which surpassed genome-wide significance ( P  < 5E-08), and 14 SNPs among them showed significant association with fracture risk 7 . However, candidate association studies of BMD or osteoporotic fracture focusing on bone remodeling related genes have produced conflicting results in different populations 8, 15 . Discordant results may be due to different populations or limited sample size used in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of OPG gene variants C950T (promoter) and C1181G (exon 1) revealed that the presence of polymorphic 1181G/950T alleles and 950 TT/1181 GG genotypes may play a role in the development of bone disease [95]. Apart from breast cancer, genetic variations in form of polymorphisms in OPG and RANKL have also been associated with bone fractures in premenopausal patients with systemic lupus erythematosis (SLE) [96]. OPG/A163G polymorphism has been suggested to contribute to the genetic regulation of bone mineral density or bone turnover markers in Slovak population and thus could increase or decrease osteoporosis risk [97].…”
Section: Opg and Genetic Polymorphismmentioning
confidence: 99%